1999
DOI: 10.1097/00001756-199908200-00003
|View full text |Cite
|
Sign up to set email alerts
|

Left-hemisphere processing of emotional connotation during word generation

Abstract: Areas of the brain's left hemisphere involved in retrieving words with emotional connotations were studied with fMRI. Participants silently generated words from different semantic categories which evoked either words with emotional connotations or emotionally neutral words. Participants repeated emotionally neutral words as a control task. Compared with generation of emotionally neutral words, generation of words with emotional connotations engaged cortices near the left frontal and temporal poles which are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 8 publications
4
36
1
Order By: Relevance
“…The only cluster that showed enhanced activation for both positive and negative over neutral stimuli was located in the left superior frontal gyrus (SFG). This frontal region is related to semantic processing [Demonet et al, 1992;Petersson et al, 2003] and processing of emotional valence during explicit semantic memory tasks [Cato et al, 2004;Crosson et al, 1999] as well as during judgements of emotional responses [Stowe et al, 2004]. According to this study, we suggest that the left SFG supports higher-level semantic processes as well as processing of emotional information.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The only cluster that showed enhanced activation for both positive and negative over neutral stimuli was located in the left superior frontal gyrus (SFG). This frontal region is related to semantic processing [Demonet et al, 1992;Petersson et al, 2003] and processing of emotional valence during explicit semantic memory tasks [Cato et al, 2004;Crosson et al, 1999] as well as during judgements of emotional responses [Stowe et al, 2004]. According to this study, we suggest that the left SFG supports higher-level semantic processes as well as processing of emotional information.…”
Section: Discussionmentioning
confidence: 52%
“…According to earlier studies on emotional word recognition, we hypothesize to find enhanced medial and lateral frontal activation for emotional over neutral stimuli [Crosson et al, 1999[Crosson et al, , 2002Kuchinke et al, 2005] with positive stimuli inducing activation in frontotemporal regions and negative information in fronto-temporal regions and posterior cingulate [Canli et al, 2004;Kuchinke et al, 2005;Mickley and Kensinger, 2008]. Moreover, as the focus of the current study is on non-emotional aspects (i.e., lexical) of the stimuli and we were interested in emotional influence across the whole brain rather than on specific regions, we did not expect activation of the amygdala in line with earlier work on semantic processing [Kuchinke et al, 2005;Liu et al, 2010;Luo et al, 2004].…”
Section: Introductionmentioning
confidence: 95%
“…Semantic processing of words is typically investigated by single word reading or listening (Binder et al, 1996(Binder et al, , 2000Cohen et al, 2002;Fiez et al, 1999;Moore and Price, 1999;Small et al, 1996;Specht and Reul, 2003), semantic categorization judgment (i.e., making a decision whether a presented stimulus is a member of a specific semantic category, such as living versus nonliving, or natural versus artificial (Binder et al, 1996(Binder et al, , 2003Braver and Bongiolatti, 2002;Buchanan et al, 2000;Heim et al, 2002;Noesselt et al, 2003;Poldrack et al, 1999;Scott et al, 2003), semantic association judgments involving words (Adams and Janata, 2002;Booth et al, 2002;Chee et al, 2000;Davis et al, 2004;McDermott et al, 2003;Noppeney and Price, 2004;Vandenberghe et al, 1996) or pictures (Adams and Janata, 2002;Chee et al, 2000;Vandenberghe et al, 1996), word generation Crosson et al, 1999), semantic retrieval (i.e., producing an object property) (Heun et al, 2000;James and Gauthier, 2004;Kelley et al, 2002;Thompson-Schill et al, 1999), and semantic priming (i.e., examining how the exposure to a stimulus influences the semantic processing of a later stimulus) (Kotz et al, 2002;Wagner et al, 2000;Wager and Smith, 2003).…”
Section: Semantic Processing Of Wordsmentioning
confidence: 99%
“…Furthermore, Hamann and Mao [30] found that, compared with neutral words, positive words significantly activated left amygdala. Besides amygdala, the prefrontal cortex and the vicinal limbic system also play an important role in processing affective meaning of words [31,32] . Moreover, Maratos et al [33] found that negative and neutral words elicited different event-related potentials (ERPs) in the left parietal and the right frontal cortex during a recognition memory task.…”
Section: The Role Of Emotion In Word Readingmentioning
confidence: 99%